2003
DOI: 10.1002/jca.10042
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial aspects of donating blood stem cells: The sibling donor perspective

Abstract: The collection of peripheral blood progenitor cells (PBPC) by apheresis has become common in related allogeneic donors. However, the acceptability of the procedure to donors has not been documented. The purpose of this baseline case series study was to evaluate the psycho-social dimensions of apheresis from the perspective of healthy sibling donors and to explore issues surrounding fully informed consent including voluntary donation. At the first interview to discuss donation, 17 consecutive human leucocyte an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(57 citation statements)
references
References 13 publications
5
52
0
Order By: Relevance
“…Most of the participants emphasized the importance of receiving comprehensive information about HLA typing and donation and the opportunity to ask questions before making their decision. This agrees with findings from other studies where sibling donors have reported a need for information (Wiener et al, 2008;Williams et al, 2003). The participants also pointed out the importance of positive care provision, having confidence in the health professionals and getting support from them and relatives before deciding whether or not to undergo HLA typing and possible donation.…”
Section: Information and Care Of Potential Sibling Donorssupporting
confidence: 88%
See 4 more Smart Citations
“…Most of the participants emphasized the importance of receiving comprehensive information about HLA typing and donation and the opportunity to ask questions before making their decision. This agrees with findings from other studies where sibling donors have reported a need for information (Wiener et al, 2008;Williams et al, 2003). The participants also pointed out the importance of positive care provision, having confidence in the health professionals and getting support from them and relatives before deciding whether or not to undergo HLA typing and possible donation.…”
Section: Information and Care Of Potential Sibling Donorssupporting
confidence: 88%
“…Earlier studies have shown that sibling donors are in a vulnerable situation (Bredeson et al, 2004;Fortanier et al, 2002;Wiener et al, 2008;Williams et al, 2003), and Study II indicates that this is true even for siblings who are unable to donate. This has also been shown in a case study (Takita et al, 2011) describing the stress experienced by a sibling who did not HLA match her ill sister.…”
Section: Information and Care Of Potential Sibling Donorsmentioning
confidence: 96%
See 3 more Smart Citations